Participação de canabinóides endógenos, da via NO/cGMP/K+ATP e do sistema noradrenérgico na antinocicepção induzida pelo exercício físico em ratos - Giovane Galdino de Souza (2012)
The antinociception induced by physical exercise has been widely investigated in the literature since the end of the 1970s. The majority of studies have demonstrated the endogenous opioid system as the main one involved in this effect. This way, knowing that there are other endogenous pathways responsible for modulate both response and impulse nociceptive, the present study aimed to investigate the participation of the endocannabinoid system, NO/cGMP/K+ATP pathway and the noradrenergic system in the antinociceptive effect induced by exercise. For the study, were used male Wistar rats submitted to an acute aerobic exercise protocol and an acute resistance exercise protocol. Moreover, were also used male 2A and 2C adrenergic receptors knockout mice and its widetype, submitted also to acute aerobic exercise protocol. The exercise protocols were performed on a treadmill adapted for rats and mice and in a weight-lifting apparatus adapted for rats. The nociceptive threshold was measured by paw withdrawal, tail-flick face-flick tests. Immediately after the exercise protocols, was found an increased significant (P<0.05) in the nociceptive threshold in all nociceptive tests after aerobic exercise and in the paw withdrawal test after resistance exercise. The respect of the involvement of the endocannabinoids system in the exercise-induced antinociception was found that the pre-injection (s.c., i.t. and i.c.v.) of CB1 and CB2 cannabinoid receptors antagonists (AM251 and AM630) reversed this effect. Furthermore, the antinociceptive effect induced by exercise protocols was potentiated and prolonged after systemic and central of enzymes degrade anandamide and 2-AG inhibitors (MAFP and JZL 184) and anandamide reuptake inhibitor (VDM 11). Following the exercise protocols was also found an increase of CB1 cannabinoid receptor expression in the brain tissue of rats quantified by Western bolt analysis. Adding to this result, the immunofluorescence technique demonstrated activation and increase in the neurons number that expressed CB1 cannabinoid receptors in the ventro lateral and dorso lateral periqueductal gray matter regions after the exercise protocols. Both exercise protocols were also responsible for increased of the endocannabinoids levels anandamide, 2-arachidonoylglycerol, palmithoylethanolamide and oleoylethanolamide in the plasma.To investigate the involvement of NO/cGMP/K+ATP in the antinociception effect induced by exercise protocols were used NOArg (non-selective inhibitor of nitric oxide synthase), the ODQ (inhibitor of cyclic guanosine monophosphate) and glibenclamide (blocker of ATP-sensitive potassium channels (K+ATP). Thus, the pre-administration s.c., i.t. and i.c.v. of these drugs reversed the antinociceptive effect found after the acute aerobic exercise and acute resistance exercise. In addition, this reversion was also found by the pre administration (s.c., i.t. and i.c.v.) of specific endothelial nitric oxide synthase inhibitor, the L-NIO; the specific inducible nitric oxide synthase inhibitor, the aminoguanidine and a specific neuronal nitric oxide synthase inhibitor, the L-NPA. Additionally, the plasma and cerebrospinal fluid levels of nitrite were increased after both exercise protocols. Also through the reagent 4-amino-5 diacetate methylamino-2'7'-difluoresceína (DAF-FM) was verified a greater release of nitric oxide (NO) in both PAG regions after the resistance exercise.However, the noradrenergic system seems to be involved only peripherally in the antinociception found after the exercise protocols. Yohimbine (a non-selective 2 adrenoreceptors antagonist), rawvolcina (a selective 2C adrenoreceptors antagonist) and BRL44408 (a selective 2A adrenoreceptors antagonist) reversed the antinociceptive effect when subcutaneously pre-injected, but when pre-injected i.t. or i.c.v the yohimbine it did not alter the antinociceptive effect induced by acute aerobic exercise and acute resistance exercise. Furthermore, after both protocols were not verified alteration in the 2C receptors expression changed in the brain tissue of rats. Thus, confirming the peripheral involvement of this system, the pre-treatment (3 days) with the guanethidine, a storage and exocytosis norepinephrine inhibitor from noradrenergic terminals, inhibited exercise-induced antinociception. In addition, the antinociception produced by the acute aerobic exercise protocol in wildtype mice was not found in 2A and 2C adrenoreceptors knockout mice. This study suggests evidence that the endocannabinoid system and NO/cGMP/K+ ATP pathway are involved in the peripheral and central antinociception induced by exercise, as well as the noradrenergic system at the peripheral level.